1989
DOI: 10.1086/167761
|View full text |Cite
|
Sign up to set email alerts
|

The chromosphere of Beta Cassiopeiae

Abstract: We have carried out high-resolution, long-wavelength ZUE observations and ground-based photometry of the 6 Scuti star Cas. The ground-based observations were used together with previous results of Antonello et al. to ensure that the ZUE observations were correctly phased relative to the photometric variation. Fluxes for the emission core of the Mg 11 k 12796 line were obtained from the ultraviolet spectra over several cycles in 1986 and 1987. We found that there is an increase in the emission during part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…On the other hand, while Lya shows a trend of elevated intensity between phases 0.25 and 0.75 compared with the phases around maximum light-similar to the behavior of the Mg ii emission suggested by Teays et al (1989)-the periodogram analysis indicates that the chromospheric emission is not persistently correlated with the ö Set cycle. The Lya flux, although affected slightly by the uncertain correction for geocoronal light, should be a much more reliable tracer of the chromospheric response to pulsational heating than the Mg n doublet: the latter is a low-contrast feature in the early F stars, and its measurement in LWP echellograms is subject to a variety of uncertainties (see Teays et al).…”
Section: The Variability Of the Ultraviolet Continuum Of Caphsupporting
confidence: 74%
See 2 more Smart Citations
“…On the other hand, while Lya shows a trend of elevated intensity between phases 0.25 and 0.75 compared with the phases around maximum light-similar to the behavior of the Mg ii emission suggested by Teays et al (1989)-the periodogram analysis indicates that the chromospheric emission is not persistently correlated with the ö Set cycle. The Lya flux, although affected slightly by the uncertain correction for geocoronal light, should be a much more reliable tracer of the chromospheric response to pulsational heating than the Mg n doublet: the latter is a low-contrast feature in the early F stars, and its measurement in LWP echellograms is subject to a variety of uncertainties (see Teays et al).…”
Section: The Variability Of the Ultraviolet Continuum Of Caphsupporting
confidence: 74%
“….7O4A ROTATIONAL MODULATION STUDY OF F STARS 707 No. 2, 1991Teays et al (1989 found phase-dependent emission in the Mg it doublet of Caph, but peaking near minimum light, contrary to the behavior cited previously for p Pup and the Cepheids.…”
Section: Caphcontrasting
confidence: 54%
See 1 more Smart Citation
“…Section 1), chromospheric activity has been reported in several other δ Scuti variables (e.g. Fracassini & Pasinetti 1982;Teays et al 1989;Fracassini et al 1991). Another apparently chromospherically active δ Scuti star, β Cas (HD 432, HR 21), is evident from Fig.…”
Section: Discussionmentioning
confidence: 60%
“…β Cas' chromosphere was studied using IUE spectra by Teays et al (1989) who found that its chromospheric activity is modulated by the pulsation and that the mean level of chromospheric activity is comparable to other F-type stars.…”
Section: Introductionmentioning
confidence: 99%